Adeus ao trabalho e aos sindicatos ou aperdadacentralidade do trabalho em Alain Touraine - Santos, Ariovaldo de Oliveira (Universidade Estadual de Londrina, 2018)
The body of articles and books that discuss the topic of the end of work is extensive and diverse. This article tries to demonstrate, through a reading of Alain Touraine, that the debate, despite being portrayed as recent, was opened in general terms in the late 1960s. Another concern of the article is to attack the way in which debate on the end of work places the discussion on the plane of immediate empirical facts, distancing itself from reflection, which provides the necessary ontological analysis that ought to accompany our understanding of the category of work. Finally, the article attempts to underscore how in the touranian debate on the end of work there is a reading of the crisis of unionism or the loss of centrality of the labor movement in contemporary capitalism.